Damage Process of Concrete Around Anchor Frame Inside Footing for Steel Pier. (2017) - Ueda, Yuji; Fujiyama, Chikako
Abstract: The purpose of this study is to investigate damage process of concrete of the footing supporting steel pier subjected to bi-directional force. A model which can reproduce complicated behavior caused by separation/contact between baseplate and anchor bolt and those between baseplate and footing concrete, was set up for three-dimensional nonlinear FE analysis. The model was verified by comparison of the relation between the bending moment and rotation angle of static loading and for cyclic loading analysis. Furthermore, analysis of the damage process inside footing concrete was performed under bi-directional loading as well as single-directional loading.